Invited Lecture 8: Innovation and Exponential Technologies in the Era of COVID 19 - Mary Boghosian (Wolters Kluwer Medknow Publications, 2020)
Brief Biosketch Prof. Mary Hrachoohi Boghosian did her PhD in "Physics of Magnetic Materials" from the University of London, Imperial College of Science and Technology, London, England, and MBA in "Innovation, Technology Planning and Management" from the Rensselaer Polytechnic Institute (RPI), School of Management and Technology, Troy, New York. She is working as Adjunct Professor at the American University of Armenia (AUA) and the California State University of Los Angeles (USA). She is also a visiting professor at the Yerevan State University, School of Journalism initiating and teaching a postgraduate-level course on the "Essentials of Creative Thinking". She spent 16 years working for NASA and the Aerospace Companies leading NASA projects and studies as well as developing the first-ever cost estimation methodology for costing very small satellites. Dr Boghosian is the author of more than forty publications and two inventions on space-related sensors and actuators. She is a recipient of several NASA technology achievement awards. In highly competitive economies, technology advancements move at an exponential pace leading to rapid change in innovation. Covid-19 has reshaped the global scientific and technological community through urgency for sharing information in research and technology development. COVID 19 has also shaped business commercialization and consumer behaviour allowing faster response and new infrastructure for technology and business development. In the midst of all this, exponential technologies supported by disruptive digitization allow companies to create their own innovation processes allowing cross industries and break down barriers. We will discuss the exponential technologies and the disruptive digitization process leading to new innovations and digital society and economy.